Privatizacija in korporativizacija javne univerze - Burcar, Lilijana (Šolsko polje, 2012)
Neoliberal capitalist states have drastically cut the already substantially shrunken or even miniscule budgets capitalist states usually set aside for public universities. The point of this budget-cutting, which represents an orchestrated attack on public universities, has been to create an artificial fiscal crisis for public universities. The aim of such policies is to force public universities to open their doors, seemingly of their own accord, to the interests and dictates of the private capital, while they themselves become transformed into commercial entities with hardly any responsibility towards the production of knowledge as common good. As public universities become hostage to the dictates of the private capital, this inevitably leads to the replacement of basic and long-term research with applied and commercially oriented, that is, fragmented and decontextualized short-term research. The inevitable result of this is that curricula themselves are eviscerated of meaningful content as the systematic pursuit of comprehensive understanding and holistic knowledge is scrapped. Public universities are forced to make up for the loss of their public budget through 1. the process of making their labour force flexible and casual and the concomitant increase of unpaid overtime workload, then through 2. the introduction of tuition fees, which leads to the creation of a new market niche for private banks while restricting the possibility of access to higher education for the majority of the population, and finally through 3. the introduction of so-called public-private partnerships, which put public universities in a subordinate position to private capital. Public-private partnerships work exclusively in favour of the interests of private capital. By transferring costly and more demanding research projects to the university facilities with an endless source of unpaid student researchers and underpaid teaching staff private companies reap very specific benefits for they no longer need to maintain and finance their own corporate research labs nor do they need to maintain and pay their own labour force. Most of these costs are transferred to the public universities for even though the corporations' donations might, at first sight, appear to involve large sums of money, these are in fact only token donations. Private companies' coverage of research and other costs is only partial at best, yet these very same private entities claim full and exclusive access to the results of such research, which is secured through the imposition of intellectual property and patent rights. This represents a classic form of usurpation and appropriation of mostly publicly funded common good, a process which is in other words described as accumulation of private capital by the population's systematic dispossession. At the same time the money that is cut back from public higher education budgets, leading to their impoverishment and structural weakening, is redirected into the creation of free-subsidies for profit-driven private faculties, which thus come to subsist on taxpayers' money.
Keywords: neoliberalism; visoko šolstvo; neoliberalizem; capitalism; kapitalizem; public university; javne univerze; privatization; privatizacija; corporativization; education; korporativizacija